Construction of an institutional space for university pedagogical advice: the experience of a federal university in the south of the state of Minas Gerais - Xavier, Amanda Rezende Costa (2023)
This article proposes to present and analyze, in the light of the theoretical framework of University Pedagogy, the process of institutional construction of a space for teaching pedagogical advice, carried out in a federal university in the state of Minas Gerais. The study is part of a broader research, of an inter-institutional nature, financed by research promotion agency, called “University Pedagogical Advice: singularities and synchronicities in an international scenario”, which aimed to systematize the concepts and practices of international university pedagogical advice, identifying singularities and synchronicities in different consolidated experiences in different institutional cultures. To carry out the study, five questionnaires were applied that dealt with empirical and identity issues, encompassing pedagogical advisors, managers and teachers who had already used this service. The data indicate an institutional process of recognition of this service as an important contribution to teacher training for the enhancement and qualification of teaching. To the same extent, challenges are identified that still need to be addressed in order to establish a process of complete legitimacy, which will consolidate the service in an institutional training territory.